FACTORS AFFECTING DECISIONS ON LENDING (STUDIES ON BPRS IN BATAM CITY) - Chasdy Novriadi; Didi Sundiman (JURNAL TERAPAN MANAJEMEN DAN BISNIS, 2021)
This study studies the factors that influence bank financing decisions with the principle 6 C method . Financial analysis helps the NPL from bank crediting the people no more than what is determined by the OJK. This type of research is descriptive qualitative, namely research that discusses describing the phenomena that occur in the location of research using qualitative data analysis. Data collection techniques include interviews, observation, documentation . While the data analysis uses qualitative descriptive techniques. Data informants consisted of 5 prospective debtors, 1 credit analyst, and a credit committee consisting of 3 people. The results of this study state that 6 C Analysis with Relationship Marketing is only 5C (Character, Capital, Capacity, Collateral, Economic Condition) that affects credit lending decisions and 1 C (Constraints) are not opposed to credit purchase decisions.